2007
DOI: 10.1158/1055-9965.epi-06-0340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Women's Health Initiative Study Publication on Hormone Replacement Therapy Use among Women Who Have Undergone BRCA1/2 Testing

Abstract: Background: Since the publication, in July 2002, of the Women's Health Initiative (WHI) study, use of hormone replacement therapy (HRT) has decreased substantially in the general population. However, little is known about the effect of WHI study results on HRT use among women at high risk of breast cancer. The purpose of this study is to compare HRT use, prepublication versus postpublication of the WHI study, among women tested for BRCA1/2 mutations. Methods: Participants were >35 years of age and had received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…More women are becoming aware of the serious side-effects and risks; hence, the use of HRT for menopausal symptoms has decreased. 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More women are becoming aware of the serious side-effects and risks; hence, the use of HRT for menopausal symptoms has decreased. 2…”
Section: Introductionmentioning
confidence: 99%
“…More women are becoming aware of the serious side-effects and risks; hence, the use of HRT for menopausal symptoms has decreased. 2 Considering the limitation of HRT, the present need is to explore new options for management of menopausal symptoms in the form of non-hormonal drug therapy and non-pharmacological measures. Many of the potential therapies warrant further study in trials with rigorous scientific designs to determine benefit and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are first indications that breast cancer incidence has started declining [6,7]. Since the publication of the Women's health initiative (WHI) study, use of hormone replacement therapy has decreased substantially in general population [8][9][10]. Clarke et al suggested that decline in the breast cancer incidence is related with the decrease in utilisation of HRT.…”
Section: Introductionmentioning
confidence: 99%
“…This was the turning point in HRT, as the number of health hazards attributed to HRT grew, practitioners discontinued routine prescriptions for this once a time very popular and rampant treatment modality and HRT use substantially decreased in the general population (Dorval et al, 2007, Hersh et al, 2004, Majumdar et al, 2004.…”
Section: Hormone Replacement Therapy: Whi Studymentioning
confidence: 99%